COVID-19 and heart failure - Tsabedze, Nqoba; Kraus, Sarah; Hitzeroth, Jens; Ntsekhe, Mpiko; Mpe, Martin; Makotoko, Makoali (SA Heart Journal, 2020)
Acute and chronic heart failure patients have a 2- to 3-fold increased risk of complicating with severe COVID-19, and these patients tend to have multiple comorbidities which are the primary aetiologies for the heart failure clinical syndrome. Furthermore, the incidence and prevalence of heart failure increases with advanced age, and advanced age is an independent risk factor for poor prognosis and mortality. The SARSCoV-2 infection also has multiple mechanisms that cause acute heart failure and precipitate acutely decompensated chronic heart failure. Additionally, the optimal management of these patients has been marred with the controversy around the use of the renin-angiotensin-aldosterone system blockers. This review provides an update on how heart failure patients should be managed during COVID-19 and summarises the existing evidence, focusing on heart failure.